Subtrochanteric periosteal chondroma: A case report and tumor overview - Dhammi, IK; Maheshwari, AV; Jain, AK; Gulati, D (Indian Journal of Radiology and Imaging, 2006)
We report a rare case of subtrochanteric periosteal chondroma in a 16 years boy. The purpose of this presentation is to stress the importance of a proper clinico-radiological and histopathological diagnosis of this lesion. Awareness of the features of this lesion helps to prevent overtreatment of this benign condition, since its differentiation with malignant lesions may be extremely difficult, even at histology; and since conservative surgery with complete excision of the lesion leads to permanent cure.
Keywords: Periosteal chondroma; subtrochanteric